Use of Discourse Markers “Okay” and “So” by Indonesian Teacher in Bilingual Elementary School: A Case Study of “Tunjung Sari” School in Bali - Dewi, Ni Kadek Indah Setya; Ayomi, Putu Nur (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This study explores the role of discourse markers (DMs) within an educational context, particularly in elementary school classrooms, and examines how these markers function in the learning process. The research focuses on a Grade 3 teacher at Tunjung Sari School, where data were collected through recorded observations of the teacher's utterances using a multi-step process: first, recording the teacher's speech; second, carefully reviewing the recordings; and third, annotating instances of DMs. The study identifies four categories of DMs and explains their functions in context, based on the frameworks of Maschler (1994) and Fung and Carter (2007). A total of 56 DMs were classified, with structural markers emerging as the most frequently used. The word okay appeared 8 times, while the word so appeared 9 times in the conversations analyzed. The prominence of structural markers is attributed to their ability to guide students by linking different parts of utterances, thereby facilitating a coherent flow of understanding during the learning process.